Idiopathic seasonal alopecia in horse: Case report - Souza A.F. (2020)
© 2020 Universidade Federal de Minas Gerais.This report describes the first case of idiopathic seasonal alopecia in a horse in Brazil. The disease is of unknown etiology, characterized by alopecic processes in the thoracic and lateral abdominal regions, in a bilaterally symmetrical way. An eight-year-old male grade horse was treated presenting hair loss in a bilaterally symmetrical manner in the arm and abdomen areas, without any other associated clinical signs. The areas with alopecia showed no pruritus, inflammation or scaling. On the epidermis, the histological evaluation presented irregular hyperplasia, hyperpigmentation, compact orthokeratosis, edema and an inflammatory infiltrate. The hair follicles were active and containing hair shaft. The case was monitored with photographic records for two consecutive years (2012 to 2014), in which the hair fall occurred at the end of autumn with spontaneous hair growth in the middle of the summer. The diagnosis was based on the history, histopathology and photographic follow-up performed. Although mentioned in the literature, this is the first clinical and pathological description of such disorder affecting an equine in Brazil.